Contribution of biomass combustion to air pollutant emissions - Gonçalves, Cátia Vanessa Maio (2012)
In Portugal, it was estimated that around 1.95 Mton/year of wood is used in residential wood burning for heating and cooking. Additionally, in the last decades, burnt forest area has also been increasing. These combustions result in high levels of toxic air pollutants and a large perturbation of atmospheric chemistry, interfere with climate and have adverse effects on health. Accurate quantification of the amounts of trace gases and particulate matter emitted from residential wood burning, agriculture and garden waste burning and forest fires on a regional and global basis is essential for various purposes, including: the investigation of several atmospheric processes, the reporting of greenhouse gas emissions, and quantification of the air pollution sources that affect human health at regional scales. In Southern Europe, data on detailed emission factors from biomass burning are rather inexistent. Emission inventories and source apportionment, photochemical and climate change models use default values obtained for US and Northern Europe biofuels. Thus, it is desirable to use more specific locally available data. The objective of this study is to characterise and quantify the contribution of biomass combustion sources to atmospheric trace gases and aerosol concentrations more representative of the national reality. Laboratory (residential wood combustion) and field (agriculture/garden waste burning and experimental wildland fires) sampling experiments were carried out. In the laboratory, after the selection of the most representative wood species and combustion equipment in Portugal, a sampling program to determine gaseous and particulate matter emission rates was set up, including organic and inorganic aerosol composition. In the field, the smoke plumes from agriculture/garden waste and experimental wildland fires were sampled. The results of this study show that the combustion equipment and biofuel type used have an important role in the emission levels and composition. Significant differences between the use of traditional combustion equipment versus modern equipments were also observed. These differences are due to higher combustion efficiency of modern equipment, reflecting the smallest amount of particulate matter, organic carbon and carbon monoxide released. With regard to experimental wildland fires in shrub dominated areas, it was observed that the largest organic fraction in the samples studied was mainly composed by vegetation pyrolysis products. The major organic components in the smoke samples were pyrolysates of vegetation cuticles, mainly comprising steradienes and sterol derivatives, carbohydrates from the breakdown of cellulose, aliphatic lipids from vegetation waxes and methoxyphenols from the lignin thermal degradation. Despite being a banned practice in our country, agriculture/garden waste burning is actually quite common. To assess the particulate matter composition, the smoke from three different agriculture/garden residues have been sampled into 3 different size fractions (PM2.5, PM2.5-10 and PM>10). Despite distribution patterns of organic compounds in particulate matter varied among residues, the amounts of phenolics (polyphenol and guaiacyl derivatives) and organic acids were always predominant over other organic compounds in the organosoluble fraction of smoke. Among biomarkers, levoglucosan, β-sitosterol and phytol were detected in appreciable amounts in the smoke of all agriculture/garden residues. In addition, inositol may be considered as an eventual tracer for the smoke from potato haulm burning. It was shown that the prevailing ambient conditions (such as high humidity in the atmosphere) likely contributed to atmospheric processes (e.g. coagulation and hygroscopic growth), which influenced the particle size characteristics of the smoke tracers, shifting their distribution to larger diameters. An assessment of household biomass consumption was also made through a national scale survey. The information obtained with the survey combined with the databases on emission factors from the laboratory and field tests allowed us to estimate the pollutant amounts emitted in each Portuguese district. In addition to a likely contribution to the improvement of emission inventories, emission factors obtained for tracer compounds in this study can be applied in receptor models to assess the contribution of biomass burning to the levels of atmospheric aerosols and their constituents obtained in monitoring campaigns in Mediterranean Europe.